2011
DOI: 10.1371/journal.pone.0019277
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Dual Color In Vivo Bioluminescence Imaging Using a New Red Codon Optimized Firefly Luciferase and a Green Click Beetle Luciferase

Abstract: BackgroundDespite a plethora of bioluminescent reporter genes being cloned and used for cell assays and molecular imaging purposes, the simultaneous monitoring of multiple events in small animals is still challenging. This is partly attributable to the lack of optimization of cell reporter gene expression as well as too much spectral overlap of the color-coupled reporter genes. A new red emitting codon-optimized luciferase reporter gene mutant of Photinus pyralis, Ppy RE8, has been developed and used in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 28 publications
1
84
0
Order By: Relevance
“…The luminescent light it emits is detectable even after passing through tissue. 12,13 This makes the signal traceable even when its origin is in the tissues beyond the skin, which allows for the use of more sophisticated methods of reporter monitoring such as bioluminescence tomography (BLT). While two-dimensional (2D) imaging allows for a rapid screening of protein expression, BLT provides detailed three-dimensional (3D) information about the anatomical location of the signal.…”
mentioning
confidence: 99%
“…The luminescent light it emits is detectable even after passing through tissue. 12,13 This makes the signal traceable even when its origin is in the tissues beyond the skin, which allows for the use of more sophisticated methods of reporter monitoring such as bioluminescence tomography (BLT). While two-dimensional (2D) imaging allows for a rapid screening of protein expression, BLT provides detailed three-dimensional (3D) information about the anatomical location of the signal.…”
mentioning
confidence: 99%
“…Similar conclusions also have been made by Mezzanotte et al on imaging the liver and prostate using a red-optimized Fluc with CBGluc (9). The lungs, the liver, the prostate, and the GIT are difficult sites to image optically due to the great tissue depth, and the use of redemitting luciferases is more adapted to imaging in these tissues, as the longer wavelength enables better penetration through living tissues (4,(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Dual-color bioluminescence has been described with red and green luciferases expressed by mammalian cells that can be separated in vivo (9). Very recently, Chang et al showed that Fluc and CBRluc, which emit distinct light wavelengths, allow simultaneous imaging of two mycobacterial strains during infection (10).…”
mentioning
confidence: 99%
“…BLI can enable simultaneous visualization of monitoring for the expression of two divergent luciferase proteins by use of their specific substrates, i.e., the dissimilarity in the substrates for each luciferase makes it possible to selectively distinguish between the luminescent reactions for each enzyme. The imaging dual luciferase gene (red codon optimized firefly luciferase and a green click beetle luciferase) activities in the same animals could reduce variations from individual differences of the experimental animals [52]. This type of experimental design is particularly useful when trying to acquire accurate, quantitative data on gene expression by simultaneously monitoring two events in real time.…”
Section: Imaging Of Bioluminescencementioning
confidence: 99%